2011
DOI: 10.1111/j.1365-4632.2011.04899.x
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity: is it a risk factor for striae distensae?

Abstract: Striae distensae was significantly more common in women who had been born prematurely than in women who had been born at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The clinical characteristics of the 179 pregnant women, consisting of 94 primiparae and 85 multiparae, participating in this study, are summarized in Table 1. Recently, striae gravidarum was significantly more common in women who had been born prematurely than in women who had been born at term [5]. Then, pregnant women delivered after 37 weeks of gestation were used as subjects of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical characteristics of the 179 pregnant women, consisting of 94 primiparae and 85 multiparae, participating in this study, are summarized in Table 1. Recently, striae gravidarum was significantly more common in women who had been born prematurely than in women who had been born at term [5]. Then, pregnant women delivered after 37 weeks of gestation were used as subjects of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore we choose 30 week's pregnancy in this study as a lower limit of pregnancy. In our previous study [7], gravidity, parity, abortion, weight and height were found to be statistically significant factors for SD. This result was similar to the findings of Thomas et al [11], who found an association with BMI where striae gravidarum was more common in the overweight women.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen, elastin and fibrillin fibers are significantly reduced in SD compared with normal skin [6]. Our previous study found a significant association between prematurity and striae in women who gave premature birth probably as a result of poor organization of the extracellular matrix in the skin and cervix [7].…”
Section: Introductionmentioning
confidence: 99%
“…Striae distensae (SD), also called stretch marks, are a common skin condition, with a prevalence ranging from 40% to 90%, depending on the studied population. Although not considered a disease, it is an unaesthetic condition that can cause psychological discomfort …”
mentioning
confidence: 99%
“…Although not considered a disease, it is an unaesthetic condition that can cause psychological discomfort. 1 Causes of SD are not completely elucidated. 2 Despite being more frequent and having earlier onset in women, SD may occur in both sexes.…”
mentioning
confidence: 99%